Determinants of cord care practices among caregivers in a level 5 facility in Kenya - Mulwa, Penina Muia; Mbugua, Ruth Gathoni; Karonjo, Jane (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally, in the year 2020, 2.4 million children died with the likelihood of a child in Sub-Saharan Africa to die in their first month after birth being ten times higher compared to that in developed countries. Infection is a leading cause of mortality among infants with a significant number being attributed to umbilical cord infections. The aim of the study was to assess cord care practices and the associated factors among mothers and care givers at the Mombasa County referral hospital in Kenya. Methods: This was a facility-based descriptive cross-sectional study conducted in the maternal child health/family planning clinic at a level 5 public health facility in Mombasa County, Kenya. Systematic random sampling was employed to select study respondents. Quantitative data was analyzed using SPSS version 21. The association of the dependent and independent variables was assessed using Pearson Chi-square statistics. A p<0.05 was considered significant at 95% CI. Results: Slightly below half (43.6%) of the respondents had practiced inappropriate cord care. Inappropriate cord care practices reported included the use of breast milk (24.3%), herbal substances (17.8%), warm salty water (16.4%), saliva (15.1%), soot (11.2%), black soil (7.9%) and coconut oil (7.2%). Socio-cultural beliefs regarding cord care were prevalent among the respondents. Socio-demographic characteristics, facility-related factors, and socio-cultural factors were associated with cord care practices (p<0.05). Conclusions: There is a need to enhance health education regarding cord care among women in the health facilities and community. Strategies to enhance scale- up of chlorhexidine use should be explored.